Impact of School Closure during the CORONA Pandemic on Behavior of Students with ASD from Their Families Point of View - Alsubaie, Malak Merrzh; Ghareeb, Reem Mahmud (Journal of Educational and Psychological Sciences, 2022)
The study aims to find out the impact of school closure during the CORONA pandemic on the behavior of students with autism spectrum disorder (ASD) from the point of view of their families. The study sample was made up of (222) families, and a descriptive method was used in this study besides a scale developed by the two researchers. The results showed no statistically significant differences in the impact of school closure during the CORONA pandemic on the behavior of students with ASD, from the point of view of their families, based on two variables: severity of the disorder and the educational stage. The results also indicated statistically significant differences, due to the gender variable in favor of females, and increased appearance of unwanted behavior, such as stereotypical behavior, screaming and crying.
Keywords: School closure; Corona pandemic; behavior of students with autism spectrum disorder